Myocilin Mutations in Patients With Normal-Tension Glaucoma - Alward, Wallace L. M. (JAMA Ophthalmol, 2019)
IMPORTANCE: Mutations in the myocilin (MYOC) gene are the most common molecularly defined cause of primary open-angle glaucoma that typically occurs in patients with high intraocular pressures (IOP). One MYOC mutation, p.Gln368Ter, has been associated with as many as 1.6% of primary open-angle glaucoma cases that had a mean maximum recorded IOP of 30 mm Hg. However, to our knowledge, the role of the p.Gln368Ter mutation in patients with normal-tension glaucoma (NTG) with an IOP of 21 mm Hg or lower has not been investigated. OBJECTIVE: To evaluate the role of the p.Gln368Ter MYOC mutation in patients with NTG. DESIGN, SETTING, AND PARTICIPANTS: In this case-control study of the prevalence of the p.Gln368Ter mutation in patients with NTG, cohort 1 was composed of 772 patients with NTG and 2152 controls from the United States (Iowa, Minnesota, and New York) and England and cohort 2 was composed of 561 patients with NTG and 2606 controls from the Massachusetts Eye and Ear Infirmary and the NEIGHBORHOOD consortium. Genotyping was conducted using real-time polymerase chain reaction that was confirmed with Sanger sequencing, the imputation of genome-wide association study data, or an analysis of whole-exome sequence data. Data analysis occurred between April 2007 and April 2018. MAIN OUTCOMES AND MEASURES: Comparison of the frequency of the p.Gln368Ter MYOC mutation between NTG cases and controls with the Fisher exact test. RESULTS: Of 6091 total participants, 3346 (54.9%) were women and 5799 (95.2%) were white. We detected the p.Gln368Ter mutation in 7 of 772 patients with NTG (0.91%) and 7 of 2152 controls (0.33%) in cohort 1 (P = .03). In cohort 2, we detected the p.Gln368Ter mutation in 4 of 561 patients with NTG (0.71%) and 10 of 2606 controls (0.38%; P = .15). When the cohorts were analyzed as a group, the p.Gln368Ter mutation was associated with NTG (odds ratio, 2.3; 95% CI, 0.98-5.3; P = .04). CONCLUSIONS AND RELEVANCE: In cohorts 1 and 2, the p.Gln368Ter mutation in MYOC was found in patients with IOPs that were 21 mm Hg or lower (NTG), although at a frequency that is lower than previously detected in patients with higher IOP. These data suggest that the p.Gln368Ter mutation may be associated with glaucoma in patients with normal IOPs as well as in patients with IOPs that are greater than 21 mm Hg.